Step-by-step explanation:
The distance traveled by train is equal to the speed times the number of hours the train ride lasted. So
distance train = speed train · time train
distance train = 65 · x
In the same way, the distance traveled in the car is equal to the speed times the number of hours, so
distance car = speed car · time car
distance car = 48 · y
The entire trip lasted 6 hours, so
x + y = 6
Solving for y, we get:
y = 6 - x
Then, the distance traveled by car is
distance car = 48 · y
distance car = 48 · (6 - x)
Finally, the total distance of the trip is equal to
distance = distance train + distance car
distance = 65 · x + 48 · (6 - x)
distacen = 65x + 48(6 - x)